The Effect of Digital Storyboards and Collaborative Learning on Students’ Narrative Writing Achievement - Asyatur Hamni; Siska Perdina (CV. Yazri Aksara Nusantara, 2026)
This study aims to examine the effect of using digital storyboards combined with collaborative learning on the narrative writing achievement of ninth-grade students at MTsN 3 Lima Puluh Kota. The study was motivated by students’ difficulties in developing ideas and organizing texts effectively in English as a Foreign Language (EFL) learning. A quasi-experimental design with a nonequivalent pretest-posttest control group was employed, involving two classes as the experimental and control groups. The treatment was conducted over eight meetings through the integration of digital storyboards and collaborative learning. Data were collected using a narrative writing test assessed with the ESL Composition Profile and analyzed using an independent samples t-test. The findings revealed a significant difference between the two groups, with the experimental group achieving higher scores, particularly in content and organization. These results indicate that the integration of digital storyboards and collaborative learning is effective in improving students’ narrative writing ability, although limitations related to sample size and duration should be considered.Penelitian ini bertujuan untuk mengkaji pengaruh penggunaan digital storyboard yang dipadukan dengan pembelajaran kolaboratif terhadap kemampuan menulis teks naratif siswa kelas IX di MTsN 3 Lima Puluh Kota. Penelitian ini dilatarbelakangi oleh kesulitan siswa dalam mengembangkan ide dan mengorganisasikan tulisan secara efektif dalam pembelajaran Bahasa Inggris sebagai bahasa asing (EFL). Penelitian ini menggunakan desain kuasi eksperimen dengan nonequivalent pretest-posttest control group design yang melibatkan dua kelas sebagai kelompok eksperimen dan kontrol. Perlakuan diberikan selama delapan pertemuan melalui integrasi digital storyboard dan pembelajaran kolaboratif. Data dikumpulkan melalui tes menulis teks naratif yang dinilai menggunakan ESL Composition Profile dan dianalisis dengan uji independent samples t-test. Hasil penelitian menunjukkan adanya perbedaan signifikan antara kedua kelompok, di mana kelompok eksperimen memperoleh skor yang lebih tinggi, terutama pada aspek isi dan organisasi.